2021
DOI: 10.1063/5.0040109
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in flexible alternating current electroluminescent devices

Abstract: Since its first discovery by Destriau in oil dispersion of ZnS:Cu phosphors, alternating current electroluminescence (ACEL) has found enormous applications in lighting, full-color displays, and optoelectronics. ACEL materials are particularly useful for constructing flexible light-emitting devices owing to their low cost and easy integration with flexible electrodes and polymer substrates. ACEL devices utilizing the phosphor-elastomer composite as the emissive layer are intrinsically stretchable/deformable, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…Under the electric field, the charge carriers in the ZnS phosphor crystal are accelerated and impact the crystal lattice, generating electron-hole pairs in the activation center, according to the principle of the hotelectron excitation. [18] When the electron-hole pairs recombine, the crystal emits characteristic light according to the different doping elements. [19] The ZnS phosphors sandwiched between the electrode plates of the capacitor are insulated from each other by the polymer binder.…”
Section: Structures and Preparation Methods Of The Lm-eldsmentioning
confidence: 99%
“…Under the electric field, the charge carriers in the ZnS phosphor crystal are accelerated and impact the crystal lattice, generating electron-hole pairs in the activation center, according to the principle of the hotelectron excitation. [18] When the electron-hole pairs recombine, the crystal emits characteristic light according to the different doping elements. [19] The ZnS phosphors sandwiched between the electrode plates of the capacitor are insulated from each other by the polymer binder.…”
Section: Structures and Preparation Methods Of The Lm-eldsmentioning
confidence: 99%
“…The amplitude and frequency composition of an electric field becomes more complex accompanied by the introduction of a large number of power electronic devices [3]. Traditional sensors are prone to resonance and need a carrier light source [4,5], while the sensors based on the electroluminescence effect have the advantages of excellent electrical insulation performance and distributed measurement [6][7][8]. Electroluminescence refers to a solid luminescence phenomenon, in which composites convert the electric energy into optical energy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although several reviews about ACEL have been reported before, most of them do not focus on flexible ACEL devices, and the display and sensing potential of flexible ACEL devices has barely been addressed. This Review presents a comprehensive and systematic presentation of flexible ACEL devices.…”
Section: Introductionmentioning
confidence: 99%